Epigenetic regulation of cardiac fibrosis. (March 2016) - Stratton, Matthew S.; McKinsey, Timothy A.
Abstract: Fibrosis is defined as excess deposition of extracellular matrix (ECM), resulting in tissue scarring and organ dysfunction. In the heart, fibrosis may be reparative, replacing areas of myocyte loss with a structural scar following infarction, or reactive, which is triggered in the absence of cell death and involves interstitial ECM deposition in response to long-lasting stress. Interstitial fibrosis can increase the passive stiffness of the myocardium, resulting in impaired relaxation and diastolic dysfunction. Additionally, fibrosis can lead to disruption of electrical conduction in the heart, causing arrhythmias, and can limit myocyte oxygen availability and thus exacerbate myocardial ischemia. Here, we review recent studies that have illustrated key roles for epigenetic events in the control of pro-fibrotic gene expression, and highlight the potential of small molecules that target epigenetic regulators as a means of treating fibrotic cardiac diseases. Highlights: Multiple epigenetic regulators have been linked to cardiac fibrosis. Small molecule inhibitors of epigenetic regulators have anti-fibrotic activity. Epigenetic therapies have potential to treat heart failure.